The role of ethylene and ROS in salinity, heavy metal, and flooding responses in rice - Steffens, Bianka (Front Plant Sci, 2014)
Plant growth and developmental processes as well as abiotic and biotic stress adaptations are regulated by small endogenous signaling molecules. Among these, phytohormones such as the gaseous alkene ethylene and reactive oxygen species (ROS) play an important role in mediating numerous specific growth or cell death responses. While apoplastic ROS are generated by plasma membrane-located respiratory burst oxidase homolog proteins, intracellular ROS are produced mainly in electron transfer chains of mitochondria and chloroplasts. Ethylene accumulates in plants due to physical entrapment or by enhanced ethylene biosynthesis. A major crop that must endure high salt and heavy metal concentrations upon flooding in regions of Asia is rice. Ethylene and ROS have been identified as the major signals that mediate salinity, chromium, and flooding stress in rice. This mini review focuses on (i) what is known about ethylene and ROS level control during these abiotic stresses in rice, (ii) how the two signals mediate growth or death processes, and (iii) feedback mechanisms that in turn regulate ethylene and ROS signaling.